(3Gdbhd GdCfjS hGdOQ GdfajS Ydi efXheI GdTjN GdQFjSs - (3eOjf Hf YHO GdQMef GdbhUhfi , GdeUQjs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYGe aUhdG Ef cd Yde eaVd HTQa Ydi ZjQg , EeG HMSH ehVhYg , hdGTc Cf GdYde GdEdgi CaVd hCTQa GdYdhe s
(3BNQgG (B:s
(3hdPdc Ce GdTjN HGdbF ai YdGLgG , hYdGLgG JdWja GdHdZe HGdefVLGJ hENQGLg HGdeSgdGJ hGdbF YfO GHJOGA GdfhHI HeG jYjf Ydi ENQLg s
(3aQZ GdeDda ef JCdjagG SfI (B1010 (3g`s
(3hGdefXheI ai (B112 (3HjJkGai BNQgG NW GdeDdas
(3hgPg GdefXheI eTJedI Ydi WHGFY GdaUhd GdCQHYI heG jMOK ai cd aUd ef VQQ Ch efaYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B183 s
Keywords: (3GdWHs